2015
DOI: 10.1111/jfbc.12114
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Extracellular Gelatinolytic Protease from B acillus Amyloliquefaciens  H11

Abstract: Extracellular gelatinolytic enzyme from Bacillus amyloliquefaciens H11 was purified by gel filtration chromatography on Sephacryl S‐200 and ion exchange chromatography on diethylaminoethyl‐cellulose with 35% yield and 14‐fold increase in purity. Based on sodium dodecyl sulfate–polyacrylamide gel electrophoresis, the molecular weight of the purified enzyme was estimated to be 21 kDa. The optimum gelatinolytic activities of purified enzyme toward porcine gelatin were 50C and pH 8.0. The inhibitor study revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
4
6
0
Order By: Relevance
“…B. amyloliquefaciens and B. methylotrophicus were the most active isolates in both TMR silages of this experiment. Their activities were mainly with serine and metallo proteinases characteristics, and similar results were also obtained by Sai-Ut et al [31] before. Proteolytic strains of other Bacillus species were isolated in lower orders of magnitudes.…”
supporting
confidence: 89%
“…B. amyloliquefaciens and B. methylotrophicus were the most active isolates in both TMR silages of this experiment. Their activities were mainly with serine and metallo proteinases characteristics, and similar results were also obtained by Sai-Ut et al [31] before. Proteolytic strains of other Bacillus species were isolated in lower orders of magnitudes.…”
supporting
confidence: 89%
“…During the present study, the enzyme from B. amyloliquefaciens HM48 was stable with pH buffers ranging from acidic to alkaline (pH 6–12), thereby reflecting that the enzyme has a wide pH spectrum reaching its maximal activity at pH 8.0, and an analogous observation has been recorded by Guleria et al [ 75 ]. However, the enzyme under examination had a much wider alkaline pH range than many previously reported B. amyloliquefaciens species having pH in the range of 5.0–11 [ 27 ], 4.0–10 [ 10 ], 4.0–10 [ 72 ], 6.0–10 [ 83 ] and 6.0–11 [ 26 ]. On the other hand, the pH-dependent enzyme stability profile of B. amyloliquefaciens HM48 (pH 8–11) also did not display much variation in the residual activity of the enzyme, thereby suggesting stability of the enzyme in alkaline pH range.…”
Section: Discussionmentioning
confidence: 94%
“…The optimal pH of B. amyloliquefaciens proteases is pH 8.0. A slight decrease in activity was found in the alkaline pH range, and a more pronounced decrease was observed in the acidic pH range . BPN and PSP proteases show similar activities at pH 8.0 and 45°C.…”
Section: Resultsmentioning
confidence: 85%
“…B. amyloliquefaciens produces large amounts of extracellular neutral metallo‐serine protease and alkaline serine protease . A previous study reported that maximum proteolytic activity was observed at 50°C, and activity gradually decreased at higher temperatures . The optimal pH of B. amyloliquefaciens proteases is pH 8.0.…”
Section: Resultsmentioning
confidence: 99%